Co-determination and innovation - Kornelius Kraft; Jörg Stank; Ralf Dewenter (Institute for the Study of Labor (IZA), 2009)
This paper examines the effect of the German co-determination law of 1976 (MitbestG) on the innovative activity of German firms. Co-determination applies to firms with 2000 employees or more. Data from 1971-1976 and 1981-1990 on 148 firms are used to compare the number of patents granted to co-determined firms before and after the introduction of the law. Several control variables are applied and in particular, in order to avoid a possible bias from specific effects of firm size, we compare the co-determined firms with others before and after 1976. The results do not support the view that co-determination slows down technological progress and reduces innovativeness.
urn:nbn:de:101:1-2009102676
Keywords: J5; L2; O3; 330; Co-determination; innovation; patents; Mitbestimmung; Innovation; Patent; Deutschland